Solidaritas Sosial Masyarakat Dalam Tradisi Mappadendang Pada Suku Bugis di Desa Paria Kecamatan Duampanua Kabupaten Pinrang - Gustia Agus (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to determine the form of community solidarity in the Mappadendang tradition of the Bugis in Paria Village, Duampanua District, Pinrang Regency and the influence of the Mappadendang tradition in coloring the joints of socio-cultural life. This research uses descriptive qualitative research with cultural anthropology and sociology approaches. This data collection technique was obtained from the field with the methods of observation, interviews, and documentation. By involving several informants, namely people who will and have carried out the mappadendang tradition, figures who guide the process of the mappadendang tradition, head of farmer groups, and the community in the location of the mappadendang tradition. Based on the research shows that: (1) the form of community solidarity in the mappadendang tradition now they always interact and live side by side. Their solidarity is very well maintained, the community can co-exist to meet their needs and encourage the community to interact and work together to change the current conditions that were initially not good for the better. Solidarity in tradition is needed because it can facilitate work and achieve certain goals. (2) the influence of the mappadendang tradition on the community is a sense of gratitude for the fortune that has been given and there is also a good influence now to improve good cooperation.